Design and Analysis of a Miniaturized Triple-Band Implantable Antenna for Biomedical Applications - Porworamon Changkol; Sopanarin Mongkolcharoensri; Keerati Kirasamutranon; Paleerat Wongchampa; Lerson Kirasamuthranon (Proceedings of International Exchange and Innovation Conference on Engineering & Sciences (IEICES), 2025)
This paper presents the design and simulation of a compact F-shaped patch antenna for implantable biomedical applications. The antenna is optimized to operate at three key frequency bands: 401–406 MHz (MICS), 1.395–1.432 GHz (WMTS), and 2.4–2.5 GHz (ISM). A progressive design approach—starting from an I-shape and evolving to an F-shape with a shorting pin—was employed to achieve multiband operation and circular polarization. Full-wave simulations were performed using CST with a realistic three-layer human tissue phantom based on the Zubal model. The final design exhibits return loss below –10 dB, stable VSWR, gain consistency, and radiation efficiency above –15 dB across all bands. Radiation pattern analysis shows a transition from omnidirectional to directional as frequency increases. The antenna also maintains robustness against implantation depth variation and supports communication distances up to 15 meters. These results demonstrate the antenna’s potential for reliable, efficient in-body wireless communication.
Keywords: Wireless Body Area Networks; Antenna Design and Analysis; Microwave Imaging and Scattering Analysis